Spatial distribution of synapses on tyrosine hydroxylase–expressing juxtaglomerular cells in the mouse olfactory glomerulus. Issue 5 (10th January 2017) - Kiyokage, Emi; Kobayashi, Kazuto; Toida, Kazunori
Abstract: Olfactory sensory axons converge in specific glomeruli where they form excitatory synapses onto dendrites of mitral/tufted (M/T) and juxtaglomerular (JG) cells, including periglomerular (PG), external tufted (ET), and superficial‐short axon cells. JG cells consist of heterogeneous subpopulations with different neurochemical, physiological, and morphological properties. Among JG cells, previous electron microscopic (EM) studies have shown that the majority of synaptic inputs to tyrosine hydroxylase (TH)‐immunoreactive neurons were asymmetrical synapses from olfactory nerve (ON) terminals. However, recent physiological results revealed that 70% of dopaminergic/γ‐aminobutyric acid (GABA)ergic neurons received polysynaptic inputs via ET cells, whereas the remaining 30% received monosynaptic ON inputs. To understand the discrepancies between EM and physiological data, we used serial EM analysis combined with confocal laser scanning microscope images to examine the spatial distribution of synapses on dendrites using mice expressing enhanced green fluorescent protein under the control of the TH promoter. The majority of synaptic inputs to TH‐expressing JG cells were from ON terminals, and they preferentially targeted distal dendrites from the soma. On the other hand, the numbers of non‐ON inputs were fewer and targeted proximal dendrites. Furthermore, individual TH‐expressing JG cells formed serial synapses, such as M/T→TH→another presumed M/T or ON→TH→presumed M/T, but not reciprocal synapses. Serotonergic fibers also associated with somatic regions of TH neurons, displaying non‐ON profiles. Thus, fewer proximal non‐ON synapses provide more effective inputs than large numbers of distal ON synapses and may occur on the physiologically characterized population of dopaminergic‐GABAergic neurons (70%) that receive their most effective inputs indirectly via an ON→ET→TH circuit. J. Comp. Neurol. 525:1059–1074, 2017. © 2017 Wiley Periodicals, Inc. Abstract : We showed that the majority of synaptic inputs from olfactory nerves (ON) to tyrosine hydroxylase (TH) neurons were on distal dendrites, whereas fewer excitatory inputs from non‐ON processes including centrifugal fibers preferentially targeted proximal dendrites. Thus TH neurons may easily evoke intraglomerular inhibition by weak ON and effective non‐ON inputs.